Continuous and Batch Production of Chloroperoxidase by Mycelial Pellets of Caldariomyces fumago in an Airlift Fermentor - Carmichael, Robert D. (1989)
Batch and continuous production of the extracellular heme glycoprotein chloroperoxidase (CPO) was studied with an airlift fermentor. We induced Caldariomyces fumago CMI 89362 to form pellets by transferring a small inoculum volume in preculture prior to growth in a 1-liter fermentor. Continuous replacement of the fructose-salts medium (dilution rate, 0.008 h(−1)) supported continuous CPO formation at an average concentration of 128 ± 10 mg of CPO liter(−1) for 8 days. Optimum CPO production rates averaged 1.2 ± 0.1 mg of CPO h(−1) at dilution rates below 0.033 h(−1). Varying the carbohydrate content of the feed solution or the time of starting the feed did not significantly alter the amount of CPO produced. Batch fermentation in the airlift fermentor resulted in maximum CPO concentrations of 280 ± 80 mg of CPO liter(−1), although on two separate occasions CPO concentrations reached 400 to 450 mg liter(−1), which was double the amount obtained by free hyphae in shake flask culture.